Recycled concrete aggregate as a medium for horizontal filter for removal of phosphorus in greywater - Adnan, Suraya Hani; Ismail, Muhammad Shafiq; Hamidon, Nuramidah; Abd Roni, Norwardatun; Mohamed Sunar, Norshuhaila; Ahmad, Faridahanim (Institute of Advanced Scientific Research, 2020)
The process of phosphorus removal from greywater in conventional methods require a combination of tertiary-level treatment system because the removal of phosphorus required a complex process. Therefore, this study is focus to identify percentage of phosphorus that can be removed through horizontal filter system by using recycled concrete aggregate (RCA). RCA was used in this study as the main materials for removing phosphorus. The concrete cube was taken from concrete laboratory and was crush by crushing machine which the sizing between 5 mm to 20 mm. In this study, it is found that excessive phosphorus was cause to eutrophication phenomena. The inclusion of phosphorus on the surface of air increasing due to industrial, domestic and agricultural activities. The effect of this condition has led to diversity of aquatic species that was be affected as well as lack of dissolved oxygen and lighting as the water surface is covered by water plants and algae. In this study, the aggregate size of 5 mm at most removal of phosphorus in greywater by 97.8% in the period to 12 days of treatment while the aggregate size 20 mm only able to get rid of phosphorus of 55.5% by dosage of RCA of 20 kg in horizontal filter. The horizontal filter can be used as alternative method for removing phosphorus in greywater.